SISTEM INFORMASI GEOGRAFIS KANTOR DINAS PEMERINTAH KABUPATEN PIDIE BERBASIS ANDROID - Cut Mutia; Habibi Habibi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Along with the times, Android-based mobile devices can provide information on the location of the Pidie district office. Android provides a complete, open, and free platform for developers to create their own Geographic Information System (GIS) that will be used by various mobile devices. In addition to using the Android Studio application as a tool to create android-based applications, to display information on the location of the Pidie district office. then this Android-based Geographic Information System is combined with maps that are processed in the Quantum Gis application. Furthermore, this application is also connected to a web application that functions as a forum for admins to input, change, delete official office data.Keywords : Android, SIG, Quantum GIS, Pidie